2018
DOI: 10.1097/md.0000000000013300
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of ruptured distal posterior inferior cerebellar artery aneurysms

Abstract: Distal posterior inferior cerebellar artery (PICA) aneurysm is a kind of rare intracranial aneurysm with controversial evidence in managements. The main purposes of this research are to study the safety and effectiveness of parent artery occlusion (PAO) compared with selective aneurysm coiling (SAC) as well as figure out factors that affect the outcomes.All characteristics of patients that diagnosed with ruptured distal PICA aneurysm and treated with endovascular management in our hospital from July 2009 to Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nevertheless, EVT related complications including intraprocedural ruptures and new-onset infarcts are not rare 33 . Chen's study even reported that the morbidity of EVT related imaging infarcts was up to 33%, most of them didn't show apparent symptoms fortunately 65 . A meta-analysis suggested PICA aneurysms treated with EVT had a higher recurrence rate and lower occlusion rate than those treated with surgery 35 .…”
Section: Aneurysmmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, EVT related complications including intraprocedural ruptures and new-onset infarcts are not rare 33 . Chen's study even reported that the morbidity of EVT related imaging infarcts was up to 33%, most of them didn't show apparent symptoms fortunately 65 . A meta-analysis suggested PICA aneurysms treated with EVT had a higher recurrence rate and lower occlusion rate than those treated with surgery 35 .…”
Section: Aneurysmmentioning
confidence: 97%
“…EVT reduces the risk of direct brainstem injury and anesthesia related complications, which is more preferable for patients with poor clinical status 34 . EVT strategies such as stand-alone coiling, stent-assisted coiling, microcatheter-assisted coiling, flow diversion, parent artery occlusion with coils were successfully used to treat PICA aneurysms 33 , 65 - 73 . The treatments of PICA dissecting aneurysms were prone to require vessels sacrifice 38 .…”
Section: Aneurysmmentioning
confidence: 99%
“…Chen et al described the periphery of the distal PICA from the tonsillomedullary segment and reported that of the 36 patients with ruptured aneurysms of the distal PICA, 28 were treated with PAO and eight underwent selective aneurysm coiling (SAC). 17) PAO resulted in lower mortality (3.57% vs. 12.5%) but higher occlusion rates (100% vs. 87.5%) than SAC. Furthermore, 12 of the patients (33%) who underwent PAO experienced new cerebral infarctions, but none showed any new neurological symptoms.…”
Section: Discussionmentioning
confidence: 84%